Hair removal treatment using 1,064 nm long-pulsed Nd:YAG laser in auricular post reconstruction of microtia patient: two case reports - Ruchiatan, Kartika; Essary, Erika Dewi; Hindritiani, Reti; Effendi, RM Rendy Ariezal; Septrina, Rani; Gunawan, Hendra; Suwarsa, Oki (Dermatology Reports, 2019)
Microtia is a congenital anomaly of the external and middle ear with various degrees of severity. The hair growth on the reconstructed auricle causes aesthetic problems. We describe two cases about the successful epilation of unwanted hair in postauricular reconstruction of microtia patients using 1,064 nm long-pulsed neodymium: ytrium-alumunium-garnet (LP Nd:YAG) laser in Fitzpatrick skin type IV patients, using 6x6 mm tip, 35 J/cm2 fluence, 10 ms pulse, and 1 Hz frequency with burnt of hair as an endpoint. On the follow up day 11 of case one and day 7 of case two, the hair reductions on treated auricles were 46% and 58%, respectively, with no adverse effects. Minimal 6 repeated sessions are recommended for optimal result. In these case reports, LP Nd:YAG laser treatment is considered effective for the unwanted hair growth on the reconstructed auricle in dark skin type patients with minimal risk of adverse effect.